Validation of principal’s innovation leadership scale using factor analysis in Malaysian school context - Syariff M. Fuad, Dayang Rafidah; Musa, Khalip; Yusof, Mat Rahimi; Swart, Bernard; Pick Dew, Ting; Kok Ming, Goh; Abdullah, Amrina Rosyada (Institute of Advanced Engineering and Science, 2025)
This study addresses the need for a standardized tool to assess innovation leadership in secondary education. Despite its importance, no established instrument exists for evaluating and developing innovation leadership among school administrators. The principal innovation leadership scale (PILS) was developed and validated to bridge this gap. The process involved a literature review, expert consultations, and an initial 58-item pool. Exploratory and confirmatory factor analysis (CFA) refined the scale to 18 items across five dimensions, demonstrating strong model fit (comparative fit index (CFI)=0.957, root mean square error of approximation (RMSEA)=0.080, incremental fit index (IFI)=0.958, normed fit index (NFI)=0.947, Tucker-Lewis’s index (TLI)=0.90). The fitted model indicated a satisfactory fit, confirming that the five latent constructs effectively measure the observed variables in the questionnaire. The PILS offers a standardized tool for assessing innovative leadership among school leaders, enabling targeted improvement strategies and informing professional development programs. This study significantly contributes to the discourse on innovation leadership in education by providing a valuable instrument for evaluating and enhancing school leadership practices.